MANIFESTASI ORAL HUMAN IMMUNE DEFICIENCY VIRUS (HIV)/ AQUIRED IMMUNO DEFICIENCY SYNDROME PADA ANAK - I Dewa Ayu Ratna Dewanti (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Introduction. These days HIV/AIDS infection is fast to children in the world. In developing countries such as Indonesia, this was caused first death and fourth in the world. Like at adult, HIV/AIDS to child can be manifestation in oral. Purposed of writing. This writing purposed for given information to medical and public for oral manifestation from AIDS to children. Writing benefit. This information expected to dentis can do protection and dental managemant with right. Discused. Oral manifestation HIV to children have different to adult. It may be relates to immune system in rough. Candidosis and necrotizing ulcerative gingivitis were oral lesion to child were HIV with hard immunosupresion. Linear erythema leukoplakia and sarcoma kaposi could indicator midle immunosupresion and hard. Magnification of paratis, herpes simplex virus infection and recurrent aphtous stomatitis not special relates to level ofimmunosupresion. Development of dental caries could be correlates with level of immunosupresion. Conclusion. BestManagement was by considering immunology status via precaution and inspection tooth and oral routinely formaintains health and reachs quality of good life.